Historical Dictionary of International Organizations - Schechter, Michael G. (Rowman & Littlefield Publishers, 2009)
One of the most pervasive phenomena that distinguish the early 21st century is the prevalence of international organizations (IOs). There are IOs in virtually every sector: political, economic, trade, social, educational, scientific, defense, and so forth. Some IOs are restricted to clearly defined activities and closely controlled by their members; others just grow and grow, moving into new sections and becoming more powerful in some ways than their members. The second edition of Historical Dictionary of International Organizations provides a comprehensive overview of the major international organizations, both intergovernmental and international intergovernmental, of the 20th and 21st centuries. While the emphasis is on organizations that continue to operate today, important organizations that have ceased to exist are also included. This reference includes a chronology, an introductory essay, and over 700 cross-referenced dictionary entries on the organizations, significant leaders, pioneers, founders and members.